Pieces of my mind : essays and criticism, 1958-2002 - Kermode, Frank, 1919- (New York : Farrar, Straus and Giroux, 2003)
A collection of essays by one of the greatest American literary critics of the twentieth century includes his writings on Don Delillo, Raymond Carver, Tom Paulin, Shakespeare, Hawthorne, and Wallace Stevens.
Includes bibliographical references and index.